691.35.2; 661.7 Kimyo va kimyoviy texnologiyalar: CORROSION RESISTANCE OF MODIFIED SULFUR CONCRETE IN VARIOUS AGGRESSIVE ENVIRONMENTS - Amanova, Nodira; Turaev, Khayit; Beknazarov, Khasan; Sottikulov, Elyor; Makhmudova, Yulduz (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, it was considered expedient to obtain sulfur concrete based on organic compounds. Silico-PB(siliko-polibutadien) and PEM(poliefirmaleinat) were used as modifiers. The corrosion resistance of the obtained samples of sulfur concrete was studied in aggressive environments, including: 10% solutions of acids H2SO4, HCl, HNO3, H3PO4, 3% solutions of Na2SO4, NaCl, NaF, 10% NaOH, pH=4-10 and machine oil, dichloroethane and diesel fuels. The results obtained in the course of research show an increase in corrosion resistance and an improvement in the mechanical properties of sulfur concrete.